Bonding Performance and Interfacial Ultra-Morphology/Nanoleakage of a Modern Self-Curing Bulk-Fill Restorative System: An In Vitro Study - Pires, Paula Maciel; Almeida Neves, Aline; Farrar, Paul; Ferrando Cascales, Álvaro; Banerjee, Avijit; Pinheiro Feitosa, Victor; Sauro, Salvatore (European Journal of Dentistry, 2025)
Objectives The objective of this study was to evaluate the bonding performance and the interfacial ultramorphology of an innovative self-curing restorative system compared with a conventional light-curing resin composite applied on dentin in etch-and-rinse (ER) or self-etch (SE) mode.Materials and Methods Twenty cavities (class I) were prepared in sound dentin and restored using two materials: (1) CERAM (n = 10; CERAM.X ONE, Dentsply Sirona) in combination with a universal adhesive system (PBU [Prime & Bond Universal]), or (2) STELA (n = 10; Stela Automix, SDI) in combination with its adhesive primer. Half of the specimens from each group were bonded in ER or SE mode. Specimens underwent microtensile bond strength testing after 24 hours of storage in artificial saliva. Failure mode was determined using a stereomicroscope, and fractographic analysis was performed using scanning electron microscopy. The interfacial ultramorphology/nanoleakage of the resin–dentin slabs was analyzed through dye-assisted confocal microscopy.Statistical Analysis For quantitative analysis, bond strength values (in MPa) were assessed for normality and variance using Kolmogorov–Smirnov and Levene's tests, followed by ANOVA based on restorative material and adhesive bonding protocol, with Fisher's least significant difference post hoc test (α = 5%).Results SE groups exhibited significantly lower bond strength (17.4 MPa for CERAM; 26.2 MPa for STELA) compared with ER groups (35.8 MPa for CERAM; 33.6 MPa for STELA) (p < 0.05). CERAM applied in SE mode showed significantly lower bond strength compared with STELA applied in SE mode. Furthermore, CERAM applied in SE mode was the only group presenting a pre-test failure rate (27%). The failure mode was predominantly mixed in ER groups and adhesive in SE groups. Nanoleakage was observed clearly in the CERAM groups applied in both ER and SE modes but was less evident in the STELA groups.Conclusion The new self-curing material (STELA) used in SE or ER may represent a promising clinical option to provide adequate interfacial adaptation and strong bonding to dentin when restoring deep class I cavities. The use of conventional adhesives in deep class I cavities may generate resin-dentin interfaces characterized by gaps and leakages.
Keywords: dentin; self-curing; dental resins; microtensile bond strength; resin–dentin interface; microscopy; confocal